2007
DOI: 10.1007/s10802-007-9167-7
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics Associated with Persistent ADHD in Late Adolescence

Abstract: This study focused on the personality characteristics associated with Attention-deficit/Hyperactivity disorder (ADHD) in a longitudinal sample of youth, with a particular focus on differences between those with and without persisting ADHD symptoms. Participants with ADHD (n = 90) were initially evaluated when they were 7-11 years old, and re-assessed at 16-22 years of age. Matched control subjects (n = 80) were recruited at the time of the follow-up evaluation. At follow-up, the Kiddie-SADS-PL, a semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 46 publications
7
53
2
2
Order By: Relevance
“…The literature has previously described that some personality traits are more prominent in ADHD populations (Martel et al, 2008;Miller et al, 2008). These differences were, however, only partly reproduced in the presented study, as the girls with ADHD exhibited higher Impulsivity compared to the normal population, consistent with previous reports (Martel et al, 2008;Miller et al, 2008), while the boys with ADHD showed higher Hedonic Capacity (as a facet of Extraversion), which has not been documented earlier. This deviation between studies may depend on the different populations or even more likely on the small sizes of the gender groups in the present study, which may have limited the statistical power and the possibilities to detect all associations.…”
Section: Personality Traits and Adherence To Medicationsupporting
confidence: 86%
See 1 more Smart Citation
“…The literature has previously described that some personality traits are more prominent in ADHD populations (Martel et al, 2008;Miller et al, 2008). These differences were, however, only partly reproduced in the presented study, as the girls with ADHD exhibited higher Impulsivity compared to the normal population, consistent with previous reports (Martel et al, 2008;Miller et al, 2008), while the boys with ADHD showed higher Hedonic Capacity (as a facet of Extraversion), which has not been documented earlier. This deviation between studies may depend on the different populations or even more likely on the small sizes of the gender groups in the present study, which may have limited the statistical power and the possibilities to detect all associations.…”
Section: Personality Traits and Adherence To Medicationsupporting
confidence: 86%
“…The severity of ADHD has been related to high Neuroticism along with low Agreeableness and Conscientiousness in young people 16 to 22 years of age (Miller, Miller, Newcorn, & Halperin, 2008). Attention difficulty symptoms have been associated with low Conscientiousness and high Neuroticism, while symptoms of hyperactivity-impulsivity with low Agreeableness in young adults (mean age 21.6) (Nigg et al, 2002).…”
Section: Personality Traits In Asthma and Adhdmentioning
confidence: 99%
“…Openness relates weakly to both dimensions, and the evidence for extraversion is mixed (see Nigg et al 2004). Regarding the latter trait, some studies have found positive relations with ADHD (Braaten and Rosén 1997;Martel et al 2010), but others have reported very weak or negative associations (Di Nicola et al 2014;Miller et al 2008).…”
Section: Relations With Personalitymentioning
confidence: 99%
“…Inter-rater reliability showed 93-100% agreement, and test-retest reliability (Cohen's ) was .80 for any anxiety disorders. The instrument had high concurrent validity when compared with questionnaires on depression, anxiety, ADHD and behavioural problems Miller, Miller, Newcorn, & Halperin, 2008). …”
Section: Ocd Diagnosis and Comorbiditymentioning
confidence: 99%